The Role of Pigment Epithelium-derived Factor in Breast Cancer Cell Metabolism - Abooshahab, Raziyeh (Curtin University, 2025)
The thesis investigates the potential of PEDF as a novel regulator of metabolism and metastasis in breast cancer. Findings highlight PEDF's critical role in modulating glucose metabolism, mitochondrial function, and metastatic progression, proposing it as a promising therapeutic target. Additionally, PEDF enhances chemotherapy effectiveness while mitigating drug resistance and side effects, underscoring its value for developing improved metabolism-based breast cancer therapies, pending further validation.